Parathyroid carcinoma in a patient with tertiary hyperparathyroidism - Paz-Ibarra, Jose Luis (2022)
Background: Most patients with terminal chronic kidney disease on hemodialysis develop secondary hyperparathyroidism. Sometimes this type of secondary hyperparathyroidism becomes severe and refractory to medical treatment, some will even develop tertiary hyperparathyroidism, the treatment of both situations is usually subtotal or total parathyroidectomy. Case Report: We present the case of a 29-year-old patient with end-stage kidney disease on hemodialysis for 13 years, who developed tertiary hyperparathyroidism, for which he underwent subtotal parathyroidectomy with half gland autotransplantation; the pathological study reported the presence of a parathyroid carcinoma in one of the four excised parathyroid glands. Conclusion: Parathyroid carcinoma is a rare neoplasm that causes primary hyperparathyroidism in less than 1% of all cases, and has been reported in some patients operated on for the development of tertiary hyperparathyroidism.